Challenges Faced by Secondary School Learners in Learning Portuguese as a Foreign Language in the Context of Zimbabwe - Masiiwa, Spencer Tinashe; Nyoni, Lisa Louisa (CV. Literasi Indonesia, 2025)
The purpose of this study was to ascertain the challenges that secondary school learners of Portuguese encounter in learning Portuguese as a foreign language in the context of Zimbabwean. Data were gathered through interviews, questionnaires, and observation. Twenty-eight participants were Form One and Form Two learners of Portuguese. The findings of the study indicated that secondary school learners experienced challenges in learning Portuguese language a foreign language. Speaking as a language skill was the difficult challenge faced by secondary school learners. The study established learner coping strategies that were employed by respondents in learning Portuguese language concepts. The use of the learner’s mother tongue was one of the common strategies employed by the learners in order to grasp and master various concepts of the Portuguese language. This study recommends further studies to be conducted on the role of the learner’s mother -tongue in the teaching and learning of Portuguese as a foreign language.